STRATEGI PENGEMBANGAN TRANSPORTASI UMUM DI KOTA MEULABOH DENGAN METODE ANALISIS SWOT - Fazlina, Rita; veranita, Veranita (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2018)
Transport is the activity of moving goods from one place to another where the activities pertaining to the transportation system an important role for every region. Meulaboh City are in the growth stage due to high urbanization rate of rapid economic growth. This has implications for the needs of the population in making be increasing to any movement. Until now, the means of public transport of passengers that already exist in Meulaboh City only public transportation for students. The absence of public transport is a particular concern that needs to be analyzed the causes of the absence of mass public transportation in Meulaboh City, the analysis is based on public perception of the needs of urban public transport. To be able answering the problems of transport in The Meulaboh City, conducted research using descriptive Qualitative Methods. This method is based on qualitative methods will be used to reinforce the assumptions of the data obtained. Units are observed as how the public perception of urban transport, judging from public demand for urban transportation, thus having known the public perception, it can be formulated in a form of? Transportation system desired by the people in Meulaboh and then determined the public transport development plans carried out by SWOT analysis to collecting internal and external factors related into the public transportation system in Meulaboh City.